TELLING ENGLISH IN A FOREIGN LANGUAGE: QUITE ANOTHER STORY - Anuchaya Montakantiwong (Indonesian JELT, 2012)
The purpose of the present study is to examine how first-year Thai undergraduate students who learn English as a Foreign Language (EFL) using referential forms in telling a coherent story in English. Participants were at intermediate level of English proficiency. Using Mayer’s wordless picture book “Frog, Where Are You?” (1969) as prompts, the participants were asked to tell the story in English. The narratives were tape-recorded and later analyzed. The data were coded on three criteria: (1) referential forms (2) discourse contexts and (3) grammatical functions. The result of the study demonstrates that Thai EFL learners employ several linguistic expressions to maintain clear reference to the characters in their narratives, one of which is using a full noun phrase when referring to a character first introduced in the story and one already mentioned. A pronoun is used if the referent is the subject of the previous clause. This finding suggests that Thai EFL learners’ referential strategies in narratives are similar to those of the native English speakers to a certain extent. Possible factors accounted for their limited linguistic abilityto achieve complete discourse cohesion in English storytellinginclude language transfer, over-explicitness, and topic discontinuity.Keywords: Thai EFL learners, referential forms, discoursecontexts, grammatical functions, narratives